Frailty is independently associated with 1-year mortality for elderly patients with non-ST-segment elevation myocardial infarction. (October 2014) - Ekerstad, Niklas; Swahn, Eva; Janzon, Magnus; Alfredsson, Joakim; Löfmark, Rurik; Lindenberger, Marcus; Andersson, David; Carlsson, Per
Background: For the large population of elderly patients with cardiovascular disease, it is crucial to identify clinically relevant measures of biological age and their contribution to risk. Frailty is denoting decreased physiological reserves and increased vulnerability. We analysed the manner in which the variable frailty is associated with 1-year outcomes for elderly non-ST-segment elevation myocardial infarction (NSTEMI) patients. Methods and Results: Patients aged 75 years or older, with diagnosed NSTEMI were included at three centres, and clinical data including judgment of frailty were collected prospectively. Frailty was defined according to the Canadian Study of Health and Aging Clinical Frailty Scale. Of 307 patients, 149 (48.5%) were considered frail. By Cox regression analyses, frailty was found to be independently associated with 1-year mortality after adjusting for cardiovascular risk and comorbid conditions (hazard ratio 4.3, 95% CI 2.4–7.8). The time to the first event was significantly shorter for frail patients than for nonfrail (34 days, 95% CI 10–58, p = 0.005). Conclusions: Frailty is strongly and independently associated with 1-year mortality. The combined use of frailty and comorbidity may constitute an important risk prediction concept in regard to cardiovascular patients with complex needs.